Otrokove koristi - pravica ali zgolj načelo Listine EU o temeljnih pravicah? - Samobor, Ana (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2021)
The EU Charter of Fundamental Rights draws a distinction between rights and principles in Articles 51(1) and 52(5). Although the distinction was one of the most important questions in the process of drafting the Charter, it fails to provide criteria for identifying rights and principles and does not clarify the legal consequences of the differentiation. The creation of clear criteria and the characterisation of a Charter provision either as a right or as a principle is, therefore, in the hands of the CJEU, but the case law leaves many questions unanswered. Article 24(2), which states that the child’s best interests must be a primary consideration in all actions relating to children, is one of the provisions the characterisation of which remains unclear. Drawing on both the existing case law and the relevant literature, the author examines the legal nature of the said provision and the legal consequences of its characterisation.
Keywords: človekove pravice; Listina EU o temeljnih pravicah; otroci; Sodišče EU; sodna praksa